Genetic characterization of 1210 Japanese pedigrees with inherited retinal diseases by whole‐exome sequencing. Issue 12 (7th November 2022) - Suga, Akiko; Yoshitake, Kazutoshi; Minematsu, Naoko; Tsunoda, Kazushige; Fujinami, Kaoru; Miyake, Yozo; Kuniyoshi, Kazuki; Hayashi, Takaaki; Mizobuchi, Kei; Ueno, Shinji; Terasaki, Hiroko; Kominami, Taro; et al.
Abstract: Inherited retinal diseases (IRDs) comprise a phenotypically and genetically heterogeneous group of ocular disorders that cause visual loss via progressive retinal degeneration. Here, we report the genetic characterization of 1210 IRD pedigrees enrolled through the Japan Eye Genetic Consortium and analyzed by whole exome sequencing. The most common phenotype was retinitis pigmentosa (RP, 43%), followed by macular dystrophy/cone‐ or cone‐rod dystrophy (MD/CORD, 13%). In total, 67 causal genes were identified in 37% (448/1210) of the pedigrees. The first and second most frequently mutated genes were EYS and RP1, associated primarily with autosomal recessive (ar) RP, and RP and arMD/CORD, respectively. Examinations of variant frequency in total and by phenotype showed high accountability of a frequent EYS missense variant (c.2528G>A). In addition to the two known EYS founder mutations (c.4957dupA and c.8805C>G) of arRP, we observed a frequent RP1 variant (c.5797C>T) in patients with arMD/CORD.